2009
DOI: 10.1037/a0016172
|View full text |Cite
|
Sign up to set email alerts
|

Workplace safety: A meta-analysis of the roles of person and situation factors.

Abstract: Recent conceptual and methodological advances in behavioral safety research afford an opportunity to integrate past and recent research findings. Building on theoretical models of worker performance and work climate, this study quantitatively integrates the safety literature by meta-analytically examining person- and situation-based antecedents of safety performance behaviors and safety outcomes (i.e., accidents and injuries). As anticipated, safety knowledge and safety motivation were most strongly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

74
1,132
2
16

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,273 publications
(1,332 citation statements)
references
References 163 publications
74
1,132
2
16
Order By: Relevance
“…This is important because workers, who do not perceive their work to be dangerous, are less likely to be motivated to engage in safe practices. Multiple studies have shown that workers who are motivated to work safely tend to work more safely, which has then been linked to fewer accidents and injuries compared to workers who work unsafely (e.g., Christian et al, 2009;Neal & Griffin, 2004). Workers may understand superficially that the work is dangerous but may not understand how dangerous it is, or they may incorrectly believe they can avoid the dangers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is important because workers, who do not perceive their work to be dangerous, are less likely to be motivated to engage in safe practices. Multiple studies have shown that workers who are motivated to work safely tend to work more safely, which has then been linked to fewer accidents and injuries compared to workers who work unsafely (e.g., Christian et al, 2009;Neal & Griffin, 2004). Workers may understand superficially that the work is dangerous but may not understand how dangerous it is, or they may incorrectly believe they can avoid the dangers.…”
Section: Discussionmentioning
confidence: 99%
“…Neal and Griffin's (2004) model is utilized for the current study of unsafe trenching practices since the model points to possible factors that could help explain why workers do not engage in proper safety behaviors. Neal and Griffin's suggestion that safety knowledge and motivation directly influence safety performance has been empirically supported (e.g., Christian, Bradley, Wallace, & Burke, 2009). Therefore, possible barriers to safe trenching and excavations include lack of knowledge of proper safe practices or lack of motivation to engage in these behaviors.…”
Section: Determinants Of Safety Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, job resources create a motivational process in which the resources motivate employees toward higher engagement (Bakker & Demerouti, 2007;Demerouti et al, 2001). Because most models of workplace safety focus on motivational processes (Christian, Bradley, Wallace, & Burke, 2009;Neal & Griffin, 2004), they are incomplete in that they do not recognize the role the health impairment process might play in workplace safety.…”
mentioning
confidence: 99%
“…Although there have been recent meta-analyses of workplace safety (Christian et al, 2009;Clarke, 2006a;Clarke & Robertson, 2005), the current meta-analysis is the first to utilize the JD-R model. This has enabled us to connect various job demands and resources to their potential impact on safety outcomes.…”
mentioning
confidence: 99%